Theology of the New Testament ; vol. 1 - Bultmann, Rudolph Karl, 1884-1976; Grobel, Kendrick (London, UK SCM, 1952)
Contents : v. 1 : The message of Jesus; The Kerygma of the earliest church; The theology of Paul. Includes bibliographical references and indexes.
Keywords: Bible. N.T. -- theology